Analisis Determinan Penggunaan e-Filling pada Wajib Pajak Orang Pribadi di KPP Pratama Lubuk Pakam - Yenni Apnilawati; Reza Hanafi Lubis; Sri Fitria Jayusman (Al-Buhuts, 2023)
This study aims to explore and analyze the factors that influence the use of e-Filling on individual taxpayers at KPP Pratama Lubuk Pakam. The type of research in this research is quantitative using a descriptive research approach with associative research. The population of this study is individual taxpayers who are registered at KPP Pratama Lubuk Pakam. The sampling method uses the Slovin formula, the number of samples used is 100 sample data. Methods of data analysis using multiple linear regression. The results showed that perceptions of security and confidentiality had a positive effect on the use of e-Filling by obtaining a t value of Security and Confidentiality of 9,301 > 2,628 with a significant level of 0.000 <0.05 then H1 was accepted and Security and Confidentiality had a positive and significant effect on the use of e-Filling, perceived convenience had a positive effect on the use of e-Filling with the obtained t value of Perceived Convenience was 8,360 > 2,628 with a significant level of 0. 000 <0.05 then H2 is accepted and Perceived Ease has a positive and significant effect on the use of e-Filling, and perceived user satisfaction has a positive effect on the use of e-Filling with the obtained t-count User Satisfaction is 4,562 > 2,629 with a significant level of 0,000 < 0.05, then H3 is accepted and user satisfaction has a positive and significant effect on the use of e-Filling.